Efficacy of wrist robot-aided orthopedic rehabilitation: a randomized controlled trial - Albanese, Giulia Aurora; Taglione, Elisa; Gasparini, Cecilia; Grandi, Sara; Pettinelli, Foebe; Sardelli, Claudio; Catitti, Paolo; Sandini, Giulio; Masia, Lorenzo; Zenzeri, Jacopo (Journal of neuroEngineering and rehabilitation, 2021)
In recent years, many studies focused on the use of robotic devices for both the assessment and the neuro-motor reeducation of upper limb in subjects after stroke, spinal cord injuries or affected by neurological disorders. Contrarily, it is still hard to find examples of robot-aided assessment and rehabilitation after traumatic injuries in the orthopedic field. However, those benefits related to the use of robotic devices are expected also in orthopedic functional reeducation.
Gesehen am 03.11.2021